2019
DOI: 10.1042/bsr20190741
|View full text |Cite
|
Sign up to set email alerts
|

Does miR-618 rs2682818 variant affect cancer susceptibility? Evidence from 10 case–control studies

Abstract: Piles of evidence have supported the relationship between miR-618 rs2682818 polymorphism and tumorigenesis, but the conclusion remains inconsistent. In the present study, we conducted a meta-analysis to sniff out the potential risk between miR-618 rs2682818 and overall cancers. Crude odds ratios (ORs) and 95% confidence intervals (CIs) analyzed by Z-test were employed to estimate the potential interrelation in five genetic models. We also prospected how the rs2682818 affects the second structure of miR-618. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The deregulation in expression levels of miR-618 may also be explanted with the appearance of genetic variants in DNA encoding this miRNA. rs2682818 is located within the stem-loop sequence of the miR-618 precursor and probably affect secondary structure and expression of mature miR-618 [ 36 ]. To explore whether different levels of miR-618 result from the presence of rs2682818 polymorphism, we performed SNP genotyping of mCC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation in expression levels of miR-618 may also be explanted with the appearance of genetic variants in DNA encoding this miRNA. rs2682818 is located within the stem-loop sequence of the miR-618 precursor and probably affect secondary structure and expression of mature miR-618 [ 36 ]. To explore whether different levels of miR-618 result from the presence of rs2682818 polymorphism, we performed SNP genotyping of mCC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another miRNA liked to human disease, miR-618, has been reported to suppress gastric cancer metastasis by downregulating transforming-growth factor beta 2 (TGF-2β) expression (Shi et al, 2019), and to inhibit prostate cancer cell migration and invasion by targeting FOXP2 and downregulating TGF-β (Song et al, 2017). Meanwhile, results of a meta-analysis study revealed that SNP rs2682818, located within the expressed sequence region of miR-618, was not associated with overall cancer risk, but was speci cally associated with breast cancer risk (Feng et al, 2019). However, in another study rs2682818 was linked to reduced CRC risk (Chen et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al [31] reported that the rs2682818 variant A allele was associated with decreased expression of mature miR-618 and increased susceptibility to follicular lymphoma. Interestingly, the rs2682818 C>A polymorphism presented a protective effect in chronic lymphocytic leukemia [47]. Chen et al found that people with AA or AC genotype had a lower risk of colorectal cancer than CC genotype [34].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that people with AA or AC genotype had a lower risk of colorectal cancer than CC genotype [34]. In addition, a recent meta-analysis study by Feng et al [47] showed that rs2682818 of miR-618 was associated with breast cancer and miR-618 could be a potential biomarker. These studies indicate that rs2682818 variant A allele can influence the miR-618 expression, thereby affecting the risk of susceptibility to some malignancies or other diseases.…”
Section: Discussionmentioning
confidence: 99%